Pengaruh Penggunaan Buku Cerita Bergambar Terhadap Kemampuan Mengungkapkan Bahasa Anak Usia Dini - Dewi, Rosi Nursila; Effendi, Endang Masluh; Nugraha, Anggi Purwa (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
This study is motivated by the low ability to express early childhood language in RA Al-Hikmah due to the less optimal use of learning media. This study aims to analyze the ability to express children's language before and after using picture storybooks and their effect on early childhood language development. The method used is an experiment with a one-group pretest-posttest design. Using a saturated sample technique, the study population included all students aged 5-6 years at RA Al-Hikmah as many as 20 people. Data were collected through observation sheets and analyzed using descriptive statistics and the Wilcoxon test for hypothesis testing. The results showed that the average ability of children in the MB category was 20% and BSB was 80%. The Wilcoxon test shows a significant value (α < 0.05), so the alternative hypothesis is accepted. This proves that the use of picture storybooks has a significant influence on the ability to express early childhood language at RA Al-Hikmah, Mekarharja Village, Purwaharja District, Banjar City.